Urokinase Levels in Urine after Nicotinic Acid Injection - Holemans, R; McConnell, D; Johnston, J.G (Thrombosis and Haemostasis, 1966)
1. Blood fibrinolytic activity and urokinase excretion were studied in a group of young healthy male subjects before and after intravenous injection of nicotinic acid. Although each of the subjects had a marked increase in blood fibrinolytic activity after injection of nicotinic acid, there was no significant change in urokinase excretion.2. These data do not support the theory that urokinase is filtered blood activator of plasminogen. It is suggested that release of urokinase into urine is primarily dependent on the time of contact between urine and walls of collecting ducts and other parts of the urine conducting system.